Open Field Layout Problem Using Hybrid Approaches: A Systematic Review - Montreano, Donny; Daihani, Dadan Umar; Septiani, Winnie; Suhardini, Didien (Universitas Ahmad Dahlan, 2025)
The Open Field Layout Problem (OFLP) is a free-configuration layout problem characterized by the absence of floor constraints and an unlimited number of potential solutions. This systematic literature review analyzed over 3,000 Scopus-indexed articles using the keyword